Terminal Value Problem for Implicit Katugampola Fractional Differential Equations in b-Metric Spaces - Salim Krim; Saïd Abbas; Mouffak Benchohra; Erdal Karapinar (Journal of Function Spaces)
This manuscript deals with a class of Katugampola implicit fractional differential equations in b-metric spaces. The results are based on the α−φ-Geraghty type contraction and the fixed point theory. We express an illustrative example.